2019
DOI: 10.1161/circoutcomes.119.005600
|View full text |Cite
|
Sign up to set email alerts
|

Racial, Ethnic, and Socioeconomic Inequities in the Prescription of Direct Oral Anticoagulants in Patients With Venous Thromboembolism in the United States

Abstract: Background: Beginning in 2012, direct oral anticoagulants (DOACs) were approved for treatment and prevention of venous thromboembolism. Prior investigations have demonstrated slow rates of adoption of novel therapeutics for black patients. We assessed the association of racial/ethnic and socioeconomic factors with DOAC use among commercially insured venous thromboembolism patients. Methods and Results: We performed a retrospective cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 32 publications
3
48
0
Order By: Relevance
“…Also consistent with previous studies, 35,36 we observed that African Americans were less likely than Whites to be prescribed newer cardiovascular agents, although differences in the frequency of comorbidities that impact drug prescribing might partially account for our observations. African American race and lower household income have been associated with lower use of newer agents, suggesting that both race and socioeconomic status affect access to novel therapies.…”
Section: Articlesupporting
confidence: 92%
“…Also consistent with previous studies, 35,36 we observed that African Americans were less likely than Whites to be prescribed newer cardiovascular agents, although differences in the frequency of comorbidities that impact drug prescribing might partially account for our observations. African American race and lower household income have been associated with lower use of newer agents, suggesting that both race and socioeconomic status affect access to novel therapies.…”
Section: Articlesupporting
confidence: 92%
“…Direct oral anticoagulants have surpassed VKAs to become the leading outpatient therapy for VTE, with 65% to 82% of patients reportedly using DOACs instead of VKAs for VTE therapy during 2012 to 2017 26,27 . Early research suggests outpatient management of DVT in the United States has increased since the release of DOACs, 28 but similar research on management of PE is lacking.…”
mentioning
confidence: 99%
“…Interestingly genotype‐guided warfarin dosing led to longer time to first therapeutic INR and overall, lower time in therapeutic range compared to a clinically guided algorithm in Black African patients requiring VKA 87 . Despite challenges with VKA management, DOACs remain under‐used in African Americans for VTE treatment in the United States, highlighting the need for improved access and affordability to cardiovascular therapeutics in an attempt to equalize outcomes after VTE among ethnoracial groups 88 …”
Section: Vte Prevention and Treatment Among Different Ethnoracial Groupsmentioning
confidence: 99%